STRATEGY OF INCREASING THE ISLAMIC TEACHERS CANDIDATE QUALITY THROUGH SOFT SKILL DEVELOPMENT IN ISLAMIC COLLEGE - M Noor Sulaiman Syah (Elementary: Islamic Teacher Journal, 2018)
The purpose of this research is to know the strategy of improving the quality of Islamic Religious Education teacher candidate in STAIN Kudus. The research method used is qualitative research method. This research used observation, interview and documentation for the data collection tools and analyzed by using interactive analysis. The result of the research shows that the strategy of improving the quality of Islamic Religious Education teachers in STAIN is divided into several strengthenings, namely strengthening of Islam, strengthening the field of PAI study, as well as the strengthening of foreign languages (English and Arabic), both through intra-curricular or co-curricular. Changes in the world of work in educational institutions should be prepared by universities preparing educators and other education personnel so that a student must be trained and trained to have the competencies described in three levels; perform, manage, and evaluate the process.